Differences of corruption types in selected Western and central-eastern health systems during the COVID-19 pandemic: a rapid review - Gonzalez-Aquines, Alejandro; Cordero-Perez, Adolfo C.; Kowalska-Bobko, Iwona (Frontiers in Public Health, 2023)
Objectives: To identify, describe, and classify the cases of health corruption present in selected Western (the Netherlands and the United Kingdom (UK)) and Central-Eastern European (Poland and Slovakia) countries during the COVID-19 pandemic. Methods: A rapid review of the literature was conducted, evaluating data from 11 March 2020 to 15 April 2021. Information sources included MEDLINE via WoS, IBSS via ProQuest, Scopus, and grey literature. Results: Thirteen cases were identified across the four countries. The primary type of health corruption in Western European countries was procurement corruption, while misuse of (high) level positions was the most prevalent in Central-Eastern European countries. Actors from central governments were most involved in cases. The rule of law and anti-corruption watchdogs reported most cases in the UK and the Netherlands, while the media reported cases in Poland and Slovakia. Conclusions: The differences in types of corruption in WE and CEE countries emphasize the need to contextualize the approach to tackle corruption. Thus, further research in preventing and tackling corruption is a vital and necessary undertaking despite the inherent of conducting health corruption research.